Youth – religion – the church in a sociological perspective. Continuations - Rusek, Halina (Przegla̜d religioznawczy, 2018)
The inspiration to pursue a research topic or to contribute to the research of other scientists often comes from a single remark, thought or sentence. ‘Continuations’ in the heading suggests that this, too, is the case of this paper. It presents early results of a research project undertaken in 2017 to examine the religiousness of high school and academic youth inhabiting different social environments and coming from different regions of Poland (the Silesian, St Cross and Lesser Poland voivodeships). Research of this kind is undertaken relatively often, and usually focuses on similar topics; was it thus necessary to add yet another new project? The inspiration behind it comes from the findings of Fr. Janusz Mariański, an expert on the religiousness of Poles, which he described in numerous publications and in particular in the latest one: Religious activity of Poles in regression, a paper which forms part of the Anniversary Publication of Prof. Andrzej Wójtowicz. In the paper, J. Mariański summarises the results of multiannual sociological research of the topic. His central thesis points to a slow but consistent diminishing - regression - of Poles’ religious activity in the past decade. Whilst it is still possible to talk about a specific uniqueness of Polish religiosity, it does not mean that it will remain so unique in the future.